Rejected stock exchange applicants - Fjesme, Sturla L.; Galpin, Neal E.; Moore, Lyndon (Journal of Financial Economics, 2021)
We examine listing applications by firms to the London Stock Exchange between 1891 and 1911. The exchange rejected 82 (13.1%) of the 628 applicants to its main board. Accepted applicants were twice as likely to pay dividends (and to pay twice as much) and had longer firm lives than rejected applicants. Rejected applicants were more likely to file for liquidation than successful applicants. These results remain even after we control for the primary benefits of the listing itself: liquidity and future capital inflows. In this era, the London Stock Exchange could screen applicants for listing.